Lithuanian geographic information infrastructure – spatial data sharing with Lithuania - Pubellier, Cindy (Geodesy and Cartography, 2012)
Geographic information system (GIS) has proved its success in the past decades by its wide utilisation bringing information together within organisations. Nevertheless, our challenge now is to use and share spatial data to its maximum advantage within the IT (Information Technology) environment instead of merely using GIS. This integration or interoperability of data is essential to information and knowledge sharing within a nation. Technology is undoubtedly crucial for the vision of National Geographic Information Infrastructure (NGII) to make interoperability happen through which tremendous economic benefits could be achieved. Of equal importance is a clear framework of agreements among government agencies, and between the government, the private sector and citizens on the terms through which the use of PSI, including geographic information, can be maximised for the benefits of all. These agreements often require attention and political support at the highest level. First published online: 03 Aug 2012